Swainsona Formosa (G.Don) Joy Thomp. Solvent Extractions Inhibit the Growth of a Panel of Pathogenic Bacteria - Chikowe, Getmore Rumbudzai; Mpala, Lindiwe Nomathemba; Cock, Ian Edwin (Pharmacognosy Communications)
Introduction: Swainsona formosa is a legumous plant which is endemic to the arid inland regions of Australia. Several Swainsona spp. were valued by the first Australian for their antiseptic properties and were used tradition- ally to treat a variety of bacterial diseases. Despite this, S. formosa solvent extractions have not been rigorously examined for antibacterial properties against many bacterial pathogens. Methods: The antimicrobial activity of S. formosa leaf extracts was investigated by disc diffusion and growth time course assays against a panel of pathogenic bacteria. The growth inhibitory activity was quantified by MIC determination. Toxicity was determined us- ing the Artemia franciscana nauplii bioassay. Results: S. formosa leaf ex- tracts inhibited the growth of a wide range of gram positive and gram nega- tive bacteria. The methanolic extracts were generally more potent than the aqueous extracts. The methanolic and aqueous S. formosa leaf extracts were particularly potent inhibitors of A. faecalis, A. hydrophilia, K. pneu- moniae, P. mirabilis, B. cereus, S. aureus and S. pyogenes growth, with MIC values substantially <1000 µg/mL and as low as 150 µg/mL against some bacteria (methanolic extract against P. mirabilis). The antibacterial activity of the methanolic and aqueous S. formosa leaf extracts was fur- ther investigated by growth time course assays which showed significant growth inhibition in cultures of all bacterial species within 1 h of exposure. All extracts were determined to be nontoxic in the Artemia franciscana nauplii bioassay, indicating their safety for therapeutic uses. Conclusions: The lack of toxicity of the S. formosa leaf extracts and their growth inhibi- tory bioactivity against a panel of pathogenic bacteria indicate their poten- tial in the development of antiseptic agents.
Keywords: Sturts Desert Pea; Fabaceae; Swainsonine; N; N-Dimethyl- tryptamine; Australian Plants; Antibacterial Activity; Medicinal Plants.